2010
DOI: 10.1007/s00464-009-0867-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of clinical leak after laparoscopic versus open bowel anastomosis

Abstract: A laparoscopic colorectal approach is not associated with a higher risk of clinical anastomotic bowel leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Some studies have identified laparoscopic surgery as a risk factor for anastomotic leakage [14] whereas others have not found any association between the approach and the incidence of anastomotic leakage [23,24]. In this study, incidence of anastomotic leakage was slightly higher in open surgery than in laparoscopic surgery though it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 63%
“…Some studies have identified laparoscopic surgery as a risk factor for anastomotic leakage [14] whereas others have not found any association between the approach and the incidence of anastomotic leakage [23,24]. In this study, incidence of anastomotic leakage was slightly higher in open surgery than in laparoscopic surgery though it did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 63%
“…Nine studies [16,21,27,29,32,37,38,40],[42] included patients with any bowel resection. These resections included ileocecal resection, other small bowel resections, segmental colectomy and subtotal colectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, while our results do not bear statistical significance, we believe the clinical results to be well worth further investigation on a large, multicenter scale. The incidence of surgical site infection following colorectal cancer operation reportedly ranges from 10 to 30 %, and the incidences of anastomotic leakage are 3-6 % in colon cancer and 3-15 % in rectal cancer [17][18][19][20][21][22]. Despite declining rates of occurrence due to advances in the operative procedures and equipment, these complications are not rare [23].…”
Section: Discussionmentioning
confidence: 95%